Science, Technology, Engineering, Mathematics - Engineering Design Process with Earthquake-Proof House Project to improve students' STEM Literacy - Anugrah, Triapani Mukti Gilang; Winarno*, Nanang; Suwarma, Irma Rahma; Fadly, Wirawan; Sihombing, Rizky Agassy (Jurnal IPA & Pembelajaran IPA, 2025)
Students' low STEM literacy level is a major challenge in 21st-century education, particularly in preparing students to face real-world problems. This study aims to examine the effectiveness of the STEM engineering design process (STEM-EDP) approach in enhancing students STEM literacy in the context of earthquake disaster mitigation. A quasi-experimental method was used with 50 eighth-grade students divided into an experimental group (28 students) and a control group (22 students). The experimental group applied the STEM-EDP approach, while the control group received conventional instruction. The results show that the STEM-EDP approach significantly improved students STEM literacy, with an average N-Gain of 0.33 (moderate category), compared to 0.23 (low category) in the control group. These findings indicate that the STEM-EDP approach enhances STEM literacy more effectively than conventional methods. This approach is relevant for addressing 21st-century challenges by integrating STEM literacy into meaningful learning experiences, particularly within the context of authentic, project-based education